The silk and spice routes. Cultures and civilizations - "Struan, Reid" (Belitha Press : UNESCO Pub: London, 1994)
One of a series which unravels the history of relations between the East and West, this book covers the story of cultures and civilizations. It explains how and why they developed and how they influenced communities they came into contact with.
Keywords: Civilisation History-Book